The Colloidal Chemical Properties and Features of the Adsorption of Functional Oligoperoxides on to Liquid and Solid Surfaces - A.S. Zaichenko; N.E. Mitina; M.O. Kovbuz; O.M. Hertsyk (Adsorption Science & Technology)
The study of the sorption processes of polyfunctional initiating systems on to organic and inorganic fillers has arisen because of the development of new filled copolymer composites. In the present study, the kinetics of formation of adsorption layers by surface-active functional oligoperoxides (FSAP) based on vinyl acetate (VA), 2-t-butylperoxy-2-methyl-5-hexene-3-yne (VEP), maleic anhydride (MAN) or maleic acid (MA) at molar ratios of VA/VEP/MA and VA/VEP/MAN equal to 1:1:1 and derived metal complexes (OMC) with a Cu 2+ ion content of 0.45% and 0.80% on the surface of glass–carbon plates were examined.